The Influence of Photoactive Heterostructures on the Photocatalytic Removal of Dyes and Pharmaceutical Active Compounds: A Mini-Review - Enesca, Alexandru; Andronic, Luminita (Nanomaterials, 2020)
The diversification of pollutants type and concentration in Wastewater has underlined the importance of finding new alternatives to traditional treatment methods. Advanced oxidation processes (AOPs), among others, are considered as promising candidate to efficiently remove organic pollutants such as dyes or pharmaceutical active compounds (PhACs). The present minireview resumes several recent achievements on the implementation and optimization of photoactive heterostructures used as photocatalysts for dyes and PhACs removal. The paper is focused on various methods of enhancing the heterostructure photocatalytic properties by optimizing parameters such as synthesis methods, composition, crystallinity, morphology, pollutant concentration and light irradiation.
Keywords: semiconductors; heterostructures; photocatalysis; dyes; pharmaceutical compounds